Caracterização do processo de furação por fricção do aço LN 700 - Pasinato, Rogério (2015)
The drilling friction aims at implementing bushings disposed without chip removal through the action of a rotary tool which promotes the heating of the material and its deformation. The application of this type of drilling is used in thin sheets to replace components with weld nuts, rivets and parts complexity that hinder access to tools for fixing. This study presents the evaluation of steel behavior HSLA LN 700 subjected to dry friction drilling, carried out in a rectangular shape with dimensions of 100 x 40 x 4mm being stuck with a manufactured tool of carbide UK 40 with nitride coating titanium, with hole diameter being obtained from 10,9mm. The literature review allowed us to evaluate the material for tool manufacturing, its geometry and parameters to be used in drilling based on previous studies in other types of materials. For the tests, two groups of rotation and advancement parameters are set to compare the results of drilling, characterized as groups 1 and 2. The drilling tests were performed in CNC machining center. With the drilling performed were evaluated results of circularity, height drained bushing region affected by temperature, hardness of the material, length of the sleeve and drained resulting residual stress of friction drilling tests. To assess the results was carried out test analysis "t", with 95% degree of reliability. The results showed that the parameters used in group 2 had better LN 700 steel behavior in the characterization of friction drilling.